2006
DOI: 10.1021/ol062711t
|View full text |Cite
|
Sign up to set email alerts
|

New Macrocyclic Compound as Chiral Shift Reagent for Carboxylic Acids

Abstract: [structure: see text] We have prepared a novel chiral macrocyclic compound 3 from a C2-symmetric aminonaphthol in a high yield. Enantiomeric acids have large nonequivalent chemical shifts (up to 0.80 ppm) in the presence of 3 in 1H NMR (500 MHz) spectra. Quantitative analyses of a series of mandelic acids with different enantiomeric purities show that host 3 is an excellent chemical shift reagent for chiral carboxylic acids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(26 citation statements)
references
References 12 publications
0
26
0
Order By: Relevance
“…1, supports the calibration curve shown. It is a well-known fact that compounds with a binaphthyl moiety tend to be good chiral shift reagents [22]. These compounds tend not to be flexible, but can form complexes in the solution easily.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1, supports the calibration curve shown. It is a well-known fact that compounds with a binaphthyl moiety tend to be good chiral shift reagents [22]. These compounds tend not to be flexible, but can form complexes in the solution easily.…”
Section: Resultsmentioning
confidence: 99%
“…Chiral derivatizing agents (CDA) continue to be an important and convenient tool for determining the enantiopurity of chiral compounds. Over the years, many authors have reported the use of these derivatizing agents on a variety of molecules such as carboxylic acids [22,23], amino alcohols [24], amines [25][26][27][28] and cyanohydrins [29,30]. Despite the fact that chiral shift reagents (CSA) do not require prior purification of modified substrates, the synthesis of CSAs continues to remain challenging, compared to the synthesis of CDAs.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, 85 exhibited an excellent ability to discriminate ( Table 7) the enantiomers of a broad variety of carboxylic acids ( Figure 9) by 1 H NMR spectroscopy. Zhang et al [70] developed a chiral shift reagent, macrocyclic compound, 85 (Scheme 13) by the simple alkylation of C2-symmetric aminonaphthol, 84 with pyridyl chloride in a high yield. Enantiomeric acids gave large nonequivalent chemical shifts (upto 0.80 ppm) in the presence of 85 in 1 H NMR (500 MHz) spectra.…”
Section: Ss-8 (R or S)-napetmentioning
confidence: 99%
“…120 Among the various functional group enclosed in macrocycle compounds, also a C 2 -symmetric aminonaphthol 29 has found application in the synthesis of a shift reagent for carboxylic acids 76,121 (Scheme 17). This is a 16 member ring product, host of a series of chiral racemic carboxylic acids.…”
Section: Chiral Shift Reagents For Carboxylic Acidsmentioning
confidence: 99%